Cisplatin resistance alters ovarian cancer spheroid formation and impacts peritoneal invasion - Powell, Lydia C.; Quintela, Marcos; James, David W.; Onyido, Emenike; Howard, David; Edwards, Kadie; Turney, Jordan L.; Morgan, Charlotte R.; Worthington, Jenny; Williams, Nicole; Dulebo, Alexander; Haschke, Heiko; et al. (Frontiers in Cell and Developmental Biology, 2025)
Epithelial ovarian cancer (EOC) is an aggressive and lethal gynaecologic malignancy due to late diagnosis and acquired resistance to chemotherapeutic drugs, such as cisplatin. EOC metastasis commonly occurs through the extensive dissemination of multicellular aggregates, formed of cells originally shed from the primary ovarian tumour, within the peritoneal cavity. However, little is known about how cisplatin resistance (CR) alters the biophysical properties of EOC multicellular aggregates and how this impacts metastasis. In this interdisciplinary study, light and atomic force microscopy was used, alongside quantitative gene and protein expression analysis, to reveal distinct differences in the biophysical properties of CR spheroids, which correlated with altered protein expression of plasminogen activator inhibitor-1 (PAI-1) and Tenascin-C. CR SKOV3 spheroids (IC50: 25.5 µM) had a significantly greater area and perimeter and were less spherical, with a reduced Young’s modulus, (p < 0.01) compared to parental (P) SKOV3 spheroids (IC50: 5.4 µM). Gene expression arrays revealed upregulation of genes associated with cell adhesion, extracellular matrix (ECM) and epithelial-to-mesenchymal transition (EMT) in CR spheroids, while immunofluorescence assays demonstrated increased protein expression of PAI-1 (p < 0.05; implicated in cell adhesion) and reduced protein expression of Tenascin-C (p < 0.01; implicated in elasticity) in CR spheroids compared to P spheroids. Furthermore, the CR spheroids demonstrated altered interactions with a surface that mimics the peritoneal lining post mesothelial clearance (Matrigel). CR spheroids were significantly less adhesive with reduced disaggregation on Matrigel surfaces, compared to P spheroids (p < 0.05), while CR cells were more invasive compared to P cells. The combined characterisation of the biophysical and biological roles of EOC multicellular aggregates in drug resistance and metastasis highlight key proteins which could be responsible for altered metastatic progression that may occur in patients that present with cisplatin resistance.